Business Building Strategies: Adaptive, Collaborative, Dynamic, and Sustainable in the Digital Era - Aang Gunawan; Yuliantini Yuliantini; Olfebri Olfebri; Lira Agusinta (Siber Nusantara of Community Service Review, 2026)
The development of digital technology has driven significant changes in the business world, requiring organizations to have the ability to adapt, collaborate, innovate, and apply sustainability principles to survive and thrive. A national seminar entitled "Business Building Strategies: Adaptive, Collaborative, Dynamic, and Sustainable in the Digital Era" was held on June 3, 2026, at the Trisakti Institute of Transportation and Logistics Campus to increase participants' understanding of relevant business strategies in facing the challenges of the digital era. This activity was attended by approximately 250 participants, consisting of students, lecturers, practitioners, business actors, and the general public. The method used included the delivery of material by competent speakers in the fields of business and digital transformation, followed by an interactive discussion and question-and-answer session. The results of the activity showed an increase in participants' understanding of the importance of adapting to technological changes, strengthening collaboration with various stakeholders, implementing sustainable innovation, and optimizing the use of digital technology in business activities. In addition, participants also gained insight into the importance of integrating economic, social, and environmental aspects in business strategies to achieve long-term sustainability. This activity makes a positive contribution in increasing the capacity of participants so that they are better prepared to face the dynamics and business opportunities in the digital era.